Application of a cold spray based 3D printing process in the production of EDM electrodes - Klarić, Štefanija; Botak, Zlatko; Hill, Damien J.; Harbidge, Matthew; Murray, Rebecca (2020)
Cold spray process principles allow the production of near-net-shape metal parts with a fast layer deposition by using 3D printing techniques via supersonic 3D deposition (SP3D). This innovative additive manufacturing process allows an easy and quick production of copper and aluminium parts with future possibilities to expand materials and alloys. The speed and materials enable the application of this cold spray based 3D printing process for the production of tools. In this paper, Electrical Discharge Machining (EDM) electrodes were fabricated by using SP3D to investigate its application in tool production. Requirements for the materials of electrodes and some existing solutions for the production of EDM electrodes with additive manufacturing methods are described first. The fabrication and experimental results are then presented for 3D printed copper EDM electrodes that were tested by using St 37-2 (DIN 17100) steel as the workpiece.
Bibliografija: 31 jed.
Summary.
Keywords: Aditivna proizvodnja -- 3D printanje -- Metali -- Hladni sprej -- Toplinska obrada